Pengaruh Minuman Kopi Minim Kafein terhadap VO2max dan Pemulihan Denyut Nadi setelah Melakukan Treadmill (The Effect of Decaffeinated Coffee Drink on VO2max and Pulse Recovery Rate after Treadmill Test) - Chikita R Hanifati; Cholis Abrori; M Ihwan Narwanto (Pustaka Kesehatan, 2016)
Coffee can be classified as a psicostimulant agent cause awakening, due to its content, such as caffeine. For intolerant person caffeine can be harmful, so nowadays created decaffeinated coffee. The purpose of this study was to determine the effect of decaffeinated coffee drink consumption on VO2max and pulse recovery rate after treadmill test. This was a quasi experimental study with Randomized Clinical Trial (RCT) methods. There were 20 volunteers, divided into two groups that swapping roles after 4 days washing out. The control group was given an instant coffee drink while the treatment group was given a decaffeinated coffee drink. All volunteers were asked to perform Modified Bruce Treadmill Test procedure until exhausted then VO2max were examined. The results showed the average value of VO2max in treatment group was +45,22 ml/kg/min and in control group +46,96 ml/kg/min from the previous study the value of VO2max using placebo was 25,98 ml/kg/min. Duration of pulse recovery rate in treatment group was 52 minutes faster than control group, 57 minutes. Analyses by T-test obtained p=0,23 mean there was no significant difference. In conclusion, decaffeinated coffee drinks could increased VO2max as the instant coffee did, but it still could accelerate pulse recovery rate. Keywords: Modified Bruce Treadmill, pulse recovery rate, VO2max, decaffeinated coffee